A data processing methodology for infrared thermography images of concrete bridges. (1st October 2017) - Hiasa, Shuhei; Birgul, Recep; Necati Catbas, F.
Highlights: This study aims to detect invisible delaminations objectively. A more objective infrared thermography data processing method was developed. IRT data was processed mathematically. Finite element model simulation was used to obtain thresholds for data processing. Integrated use of FE modeling can improve the efficiency of IRT data analysis. Abstract: This study presents a methodology to improve the usability and efficiency of infrared thermography (IRT) for subsurface damage detection in concrete structures. A practical and more objective approach to obtain a threshold for IRT data processing was developed by incorporating finite element (FE) model simulations. Regarding the temperature thresholds of sound and delaminated areas, the temperature of the sound part was obtained from the IR image, and the temperature of the delaminated area was defined by FE model simulation. With this methodology, delaminated areas of concrete slabs at 1.27 cm and 2.54 cm depths could be detected more objectively than by visually judging the color contrast of IR images. However, it was also found that the boundary condition affects the accuracy of the method, and the effect varies depending on the data collection time. On the other hand, it can be assumed that the influential area of the boundary condition is much smaller than the area of a bridge deck in real structures; thus, it might be ignorable on real concrete bridge decks. Even though there are some limitations, this methodology performed successfully paving the way towards automated IRT data analysis for concrete bridge deck inspections.